Evelyn in transit : a novel - Guterson, David (W. W. Norton & Company, Inc., 2026)
Radically open-minded, formidably strong, and unusually clear-eyed about herself and others, Evelyn Bednarz has always been a misfit. She's easily bored, unsuited to life at school, asks odd questions about faith and time, and sees through conventions others take for granted. Seeking to be true to herself, she hitchhikes across the American West taking odd jobs. In distant Tibet, another life unfolds as remote from Evelyn's as can be: the life of a boy named Tsering, raised as a Buddhist monk in the mountains, who eventually becomes a high lama. And yet, their lives are strangely linked - as Evelyn discovers when a trio of Buddhist lamas show up at her door to announce that her five-year-old son Cliff is the seventh reincarnation of the illustrious Norbu Rinpoche, recently deceased. The lamas' visit sets off a family crisis and a media firestorm over Cliff's future. Written in a spare, precise style of extraordinary beauty, full of humor, 'Evelyn in Transit' delivers much-needed insight and compassion about humanity's strivings for transcendence, and what it might mean to "live the right way."